Respostas
respondido por:
3
AP² = (4 - x)² + (- 2 - 2)² = 16 - 8x + x² + 16 = x² - 8x + 32
AP = √(x² - 8x + 32)
BP² = (2 - x)² + (- 8 - 2)² = 4 - 4x + x² + 100 = x² - 4x + 104
BP = √(x² - 4x + 104)
Como AP = BP, temos:
√(x² - 8x + 32) = √(x² - 4x + 104)
Quadrando ambos os membros
[√(x² - 8x + 32)]² = [√(x² - 4x + 104)]²
x² - 8x + 32 = x² - 4x + 104
x² - x² - 8x + 4x = 104 - 32
- 4x = 72
x = 72/(- 4) = - 18
AP = √(x² - 8x + 32)
BP² = (2 - x)² + (- 8 - 2)² = 4 - 4x + x² + 100 = x² - 4x + 104
BP = √(x² - 4x + 104)
Como AP = BP, temos:
√(x² - 8x + 32) = √(x² - 4x + 104)
Quadrando ambos os membros
[√(x² - 8x + 32)]² = [√(x² - 4x + 104)]²
x² - 8x + 32 = x² - 4x + 104
x² - x² - 8x + 4x = 104 - 32
- 4x = 72
x = 72/(- 4) = - 18
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás